2021
DOI: 10.1007/s12053-021-10007-8
|View full text |Cite
|
Sign up to set email alerts
|

Selection of priority energy efficiency practices for industrial steam boilers by PROMETHEE decision model

Abstract: savings potential, environmental benefit, cross-media effects, and payback period. As a result, some EEPs such as reuse of condensate, maintenance and repair of steam traps, insulation of steam boilers, and distribution systems were found as priority EEPs. Surprisingly, it was concluded that heat recovery from waste flue gases, economizer installation, and heat recovery from blow down have lower priority. The results showed that prevention-oriented practices were higher priority than pollution control and reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Demirel et al [61] also analyzed energy efficiency using PROMETHEE. Still, the authors' model focuses on analyzing only industrial steam boilers, differently from the model of this study that considers organizational levels.…”
Section: Discussionmentioning
confidence: 99%
“…Demirel et al [61] also analyzed energy efficiency using PROMETHEE. Still, the authors' model focuses on analyzing only industrial steam boilers, differently from the model of this study that considers organizational levels.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-criteria decision model (MCDM) was used to determine which of the two C/N ratio scenarios was more beneficial (Demirel et al 2021). This model includes a total of 4 basic phases:…”
Section: Multi-criteria Decision Model-prometheementioning
confidence: 99%
“…However, the concept of best practice operation in the context of foundries has not been sufficiently investigated in previous literature. Operational practices have been shown to impact the industry's performance and potential energy efficiency [27]. Previous studies have suggested that induction furnaces may experience up to 25 -30 % losses due to unfavorable operation [28], considering that the majority of energy consumption in the foundry is consumed in the melting process; this presents a significant gap in the literature for promoting energy-efficient operation in the foundry.…”
Section: Energy Efficiency In Foundry Productionmentioning
confidence: 99%